CASTE DEVELOPMENTAL PATHWAYS OF Cortaritermes fulviceps (BLATTODEA, TERMITIDAE). - Annoni, Giovana Mariela; Coronel, Juan Manuel; Laffont, Enrique Rafael (REVISTA DE AGRICULTURA, 2017)
The study of the developmental pathways in termites contributes to the understanding of caste evolution and resources utilization, as well as other ecological aspects. In this paper, the caste developmental pathways of Cortaritermes fulviceps (Silvestri) were analyzed in natural colonies from the Province of Corrientes, Argentina. Five measurements were taken of different body parts of larvae (L), workers (W), pre-soldiers (PS), soldiers (S), nymphs (N) and alates (A) for morphometric analyses. Dissections were also performed to determine the sex of workers and soldiers. The collected data were analyzed using principal component analysis, analysis of variance and Tukey test. In the nymphal line, four nymphal instars and alates were identified. The apterous line included two larval instars. Major workers were females and minor workers, pre- soldiers and soldiers were males. The results suggest that the developmental pathways of C. fulviceps is similar to the one of the genus Nasutitermes Dudley.